Pengolahan Limbah Jagung sebagai Bahan Bakar Alternatif - Praharsiwi, Caecilia Santi (Jurnal Atma Inovasia, 2022)
Abstract — Banaran Village is a village located in Playen District, Gunungkidul Regency, Special Region of Yogyakarta. There are a lot of potential from various sectors in Banaran Village, such as the agricultural, tourism and social-culture sector. The agriculturan sector has abundant natural products like corn or maize, while in the tourism sector there is a magnificent  forest called Wanagama Forest  that are home to a variety of flora and fauna. The social-culture sector in this village has 2 cultures that have been carried out from generation to generation, called Gejog Lesung and Tradisi Bersih-Bersih. In terms of potential sector, the authors see that corn has more potential because it can be used as an alternative energy such as bioethanol. The authors use descriptive qualitative methods for preparation of this program by describing the existing data and facts. This program can be use by the people of Banaran Village and inspire them by having new ideas, innovation and knowledge to develop and making bioethanol from corn waste. This program is expected to help people of Banaran Village to become more advanced by developing and running this program, also by using this program the authors hope that it can help Banaran Village by creating new jobs, increasing economic income and encouraging Banaran Village to become known for the program.Keywords — Banaran Village, Wanagama Forest, Corn Waste, Bioethanol Abstrak— Desa Banaran adalah sebuah desa terletak di Kecamatan Playen, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta. Desa Banaran memiliki banyak potensi dari berbagai sektor, seperti sektor pertanian, pariwisata dan sosial budaya. Sektor pertanian Desa Banaran memiliki hasil alam berupa tanaman jagung yang melimpah, sedangkan  pada sektor pariwisata Desa Banaran mempunyai hutan indah yang menjadi banyak tempat tinggal aneka ragam flora fauna, yaitu Hutan Wanagama. Sektor budaya Desa Banaran memiliki 2 kebudayaan yang telah dilakukan secara turun temurun yaitu Gejog Lesung dan Tradisi Bersih – Bersih. Namun pada segi potensi budaya, penulis melihat adanya potensi lebih dari tanaman jagung karena bisa dimaanfaatkan untuk menjadi bahan bakar alternatif dari bioetanol ini. Penulis menggunakan metode kualitatif deskriptif untuk penyusunan program kerja ini dengan memaparkan data – data dan fakta yang ada.  Program kerja ini dapat dimaanfaatkan oleh masyarakat Desa Banaran itu sendiri dengan mendapatkan banyak ide, inovasi dan edukasi untuk mengembangkan bio-etanol yang berasal dari limbah tanaman jagung. Program ini diharapkan dapat membantu Desa Banaran menjadi desa yang lebih maju dengan menjalankan dan mengembangkan program ini, serta dengan memanfaatkan program ini semoga dapat membantu masyarakat Desa Banaran dengan membuka lapangan pekerjaan, meningkatkan pendapatan ekonomi dan mendorong Desa Banaran menjadi terkenal akan program itu.Kata Kunci—.Desa Banaran, Hutan Wanagama, Limbah Jagung, Bioetanol